Elliptic fourier analysis of leaf outline differences between and among sixteen species of Hoya - Torres, Mark Anthony J.; Demayo, Cesar G.; Siar, Simeona V. (2008)
This study illustrates the utility of elliptic Fourier analysis, an outline method of shape analysis, as a tool in describing leaf shape variation in Hoya. Leaf contours of 16 species of Hoya were compared using this type of outline analysis. Detailed examinations of the leaves were done by performing three separate analyses: one for the overall shape variation using all Fourier descriptors and one each for the symmetric and asymmetric coefficients of the shape descriptors. Leaf shape variation within species was found to be continuous and, because of this, traditional approaches may not be enough to describe the extent of leaf shape diversity within or among taxa. Independent aspects of shape variation were also identified, where more than 96% were related to symmetrical variations that included differences in the length-to-width ratio, location of the widest portion of the leaf, tip shape and width near the leaf base. Five asymmetrical variations were scored which included overall asymmetry (wider on left vs. right), base asymmetry and tip asymmetry. Few leaf shape types were found based on the cluster analysis of the group centroids derived from discriminant analysis and reconstruction of the mean leaf shapes per species, suggesting structural constraints in leaf shape evolution in this group of plants.
Keywords: Hoyas (Flower)